“Your Loyalty is Rewarded”: a study of Hotel Loyalty Program in Malaysia - Chong, Daniel Ka Leong * (Universiti Teknologi MARA, 2017)
Hotel loyalty programs had shown their importance in the global market and Malaysia is following up this trend. Yet, many of the information from the perspective of customers are still yet to be discovered by researchers. The purpose of this study is to discover the current state of satisfaction and perception of hotel loyalty program and finding out the more preferred program attributes as well as the significant factor associated with the level of satisfaction in the context of Malaysia. A total of 109 survey responses were collected. The result had shown that Malaysian consumers were overall rather satisfied with the current hotel loyalty program and their satisfaction was found highly correlated with the reward value and reward timing provided which was also ranked as most important by the respondents. This study concluded that Malaysians were mostly seeking for direct or immediate reward like monetary discount and least favoured on point collection program. Lastly, the Malaysian users were found to have a positive perception on hotel loyalty program that they found the program to be useful and able to provide benefit or advantage to them.